Undernutrition was a prevalent clinical problem among older adult patients with heart failure in a hospital setting in Northwest Ethiopia - Ahmed, Hussen; Tadesse, Abilo; Alemu, Hailemaryam; Abebe, Alula; Tadesse, Melaku (Frontiers in Nutrition, 2022)
Background: Undernutrition is a frequently noticed medical problem in patients with heart failure. It is caused by poor nutrient intake, malabsorption, systemic inflammation, neurohumoral activation, oxidative stress, and hypermetabolic state. Undernutrition results in a decrease in quality of life and survival in patients with heart failure. There is a paucity of documentation on undernutrition among patients with heart failure in sub-Saharan African countries. The study aimed to determine predictors of undernutrition in heart failure patients. Methods: A cross sectional study was conducted at the University of Gondar hospital, Northwest Ethiopia, between June 1, 2021 and October 31, 2021. A consecutive sampling method was used to recruit 262 study subjects. Mini Nutritional Assessment (MNA-FL) Questionnaire was used to extract nutritional information among heart failure patients. Heart failure patients, who scored MNA-FL score < 17, were declared to have undernutrition. The Data were entered into EPI Info version 4.6.0.0, and then exported to SPSS version 26 for analysis. Explanatory variables associated with undernutrition in heart failure patients were analyzed by applying logistic regression model. P-value <0.05 was used to declare significant association. Results: A total of 262 patients with heart failure were included in the study. The mean age (±SD) of study subjects was 64.6 (±9.2) years. Hypertensive heart disease (111/262, 42%) was the commonest cause of heart failure. Based on MNA-FL score for nutritional status, 75/262 (28.6%, 95% CI: 22.9-34.4%) were undernourished (MNA-FL <17), while 124/262 (47.3%, CI: 41.5-53.1%) were at risk of undernutrition (MNA-FL=17-23.5). The remaining, 63/262 (24.1%, 95% CI: 18.2-29.8%) study subjects were well nourished (MNA-FL >24). On multi-variate analysis, patients with severe heart failure (NYHA functional class III and IV) (AOR=4.287, CI: 2.012-9.134, P-value<0.001), duration of illness 3-5 years (AOR=3.225, CI: 1.138-9.137, P-value=0.028), duration of illness > 5 years (AOR=4.349, CI: 1.592-11.879, P-value=0.001), presence of comorbidities (AOR=2.29, CI: 1.06-4.96, P-value= 0.036), treatment with loop diuretics (AOR=2.983, CI: 1.407-6.326, P-value=0.040), and rural residence (AOR=5.119; CI: 2.481-10.560, P-value<0.001) were at risk of developing undernutrition. Conclusion: Undernutrition was a significant clinical problem in older patients with heart failure. Nutritional interventions should be prioritized to patients with chronic and severe heart failure.